2002
DOI: 10.1016/s1062-1458(02)00632-3
|View full text |Cite
|
Sign up to set email alerts
|

Out-of-hospital cardiac arrest in men and women

Abstract: Background-The incidence of sudden cardiac death is roughly 3 times greater in men than in women. However, in patients treated for out-of-hospital cardiac arrest, the relationships between sex and survival after adjustment for age and cardiac rhythm are unclear. Methods and Results-In this retrospective cohort study, we examined 7069 men and 2582 women who were treated for out-of-hospital cardiac arrest in Seattle and suburban King County between 1990 and 1998. We compared successful prehospital resuscitation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
71
3
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(83 citation statements)
references
References 8 publications
6
71
3
3
Order By: Relevance
“…In the present study, among patients with primary cardiac arrest who underwent resuscitation, women had a lower prevalence of VF and a higher rate of pulseless electrical activity as the presenting arrhythmia. This trend is similar to previously reported findings (18). There were no differences between genders with respect to the overall survival rate.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, among patients with primary cardiac arrest who underwent resuscitation, women had a lower prevalence of VF and a higher rate of pulseless electrical activity as the presenting arrhythmia. This trend is similar to previously reported findings (18). There were no differences between genders with respect to the overall survival rate.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, the gender difference in SCD occurrence was low (57% male vs. 43% female), whereas most studies of primary cardiac arrest have reported a threefold higher incidence in men compared with women (18). This probably reflects the differences in the way cases were ascertained and defined in the two types of populations.…”
Section: Discussioncontrasting
confidence: 65%
“…There were some differences in the demographics of the two cohorts, but these are unlikely to explain the observed effect. Women have had either equivalent or improved outcomes during resuscitation in previous studies (37)(38)(39)(40)(41)(42)(43)(44)(45), and, while there is a paucity of data about obesity and CPR, obesity in general is associated with worse cardiovascular outcomes, a trend opposite to that seen in this study (46). The regression analysis supported the concept that these differences and that of ACE inhibitor use could not explain the change in outcome after program initiation.…”
Section: Discussionsupporting
confidence: 67%
“…to have less initial shockable rhythm 19,20 and less bystanderwitnessed SCA, 19,21 two keys factors usually associated with low survival. However, some studies observed a survival advantage for women 22,23 .…”
Section: Introductionmentioning
confidence: 99%